2005
DOI: 10.1021/cr050993p
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and Organic and Inorganic Reactivity of Metal-Coordinated Phosphinoenolates and Related Functional Phosphine-Derived Anions

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 124 publications
1
94
0
Order By: Relevance
“…It was rapidly found that when this ligand is coordinated to a transition metal, either j , weak bases being sufficient as a result of the enhanced acidity of the PCH 2 protons upon coordination [26]. This observation appeared very promising, in particular in view of the remarkable properties of nickel complexes containing such phosphino-enolate and related ligands in catalytic ethylene oligomerization, which form the basis of the industrial Shell Higher Olefin Process (SHOP) .…”
Section: Metal Complexes With Po-type Ligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was rapidly found that when this ligand is coordinated to a transition metal, either j , weak bases being sufficient as a result of the enhanced acidity of the PCH 2 protons upon coordination [26]. This observation appeared very promising, in particular in view of the remarkable properties of nickel complexes containing such phosphino-enolate and related ligands in catalytic ethylene oligomerization, which form the basis of the industrial Shell Higher Olefin Process (SHOP) .…”
Section: Metal Complexes With Po-type Ligandsmentioning
confidence: 99%
“…À were shown to carry significant electronic density at the a-PCH carbon and this was evidenced by reactions with a number of organic and inorganic electrophiles [26]. A remarkably facile reversible binding reaction of CO 2 by a Pd(II) complex under ambient conditions was discovered and its application to the catalytic telomerization of butadiene with CO 2 [50,51], and carbon-carbon bond formation by insertion of organic isocyanates RN=C=O into the a-PC-H bond [52] were some of the outcome of these investigations.…”
Section: O)oet]mentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of PPh 2 Cl with primary amines in the presence of NEt 3 represents a simple and efficient synthetic method for the preparation of a-aminophosphines. [1] The commercial availability of a large number of functionalized amines facilitates the fine tuning of the stereoelectronic properties of this class of ligands.…”
Section: Introductionmentioning
confidence: 99%